Cancer Cells Can Exhibit a Sparing FLASH Effect at Low Doses Under Normoxic In Vitro-Conditions - Adrian, Gabriel; Konradsson, Elise; Beyer, Sarah; Wittrup, Anders; Butterworth, Karl T.; McMahon, Stephen J.; Ghita, Mihaela; Petersson, Kristoffer; Ceberg, Crister (Frontiers in Oncology, 2021)
Background: Irradiation with ultra-high dose rate (FLASH) has been shown to spare normal tissue without hampering tumor control in several in vivo studies. Few cell lines have been investigated in vitro, and previous results are inconsistent. Assuming that oxygen depletion accounts for the FLASH sparing effect, no sparing should appear for cells irradiated with low doses in normoxia. Methods: Seven cancer cell lines (MDA-MB-231, MCF7, WiDr, LU-HNSCC4, HeLa [early passage and subclone]) and normal lung fibroblasts (MRC-5) were irradiated with doses ranging from 0 to 12 Gy using FLASH (≥800 Gy/s) or conventional dose rates (CONV, 14 Gy/min), with a 10 MeV electron beam from a clinical linear accelerator. Surviving fraction (SF) was determined with clonogenic assays. Three cell lines were further studied for radiation-induced DNA-damage foci using a 53BP1-marker and for cell cycle synchronization after irradiation. Results: A tendency of increased survival following FLASH compared with CONV was suggested for all cell lines, with significant differences for 4/7 cell lines. The magnitude of the FLASH-sparing expressed as a dose-modifying factor at SF=0.1 was around 1.1 for 6/7 cell lines and around 1.3 for the HeLasubclone. Similar cell cycle distributions and 53BP1-foci numbers were found comparing FLASH to CONV. Conclusion: We have found a FLASH effect appearing at low doses under normoxic conditions for several cell lines in vitro. The magnitude of the FLASH effect differed between the cell lines, suggesting inherited biological susceptibilities for FLASH irradiation.